2012
DOI: 10.1186/1472-6920-12-123
|View full text |Cite
|
Sign up to set email alerts
|

“Who writes what?” Using written comments in team-based assessment to better understand medical student performance: a mixed-methods study

Abstract: BackgroundObservation of the performance of medical students in the clinical environment is a key part of assessment and learning. To date, few authors have examined written comments provided to students and considered what aspects of observed performance they represent. The aim of this study was to examine the quantity and quality of written comments provided to medical students by different assessors using a team-based model of assessment, and to determine the aspects of medical student performance on which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
1
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 39 publications
1
11
1
4
Order By: Relevance
“…Amongst similar reported themes from our subjects, participants in the Nofziger et al study remembered having received feedback on ‘being too quiet’, ‘harder challenges’, ‘overconfidence’, ‘knowing your limits’, ‘low self‐esteem’ and ‘low self‐confidence’. Another study of third‐year medical students, this time by White and Sharma , reported similar written peer feedback themes as our clinical BDS 5 students. Amongst these, they mentioned information management, initiative and self‐direction, asking questions to learn, confidence, compassion and respect for others.…”
Section: Discussionsupporting
confidence: 65%
“…Amongst similar reported themes from our subjects, participants in the Nofziger et al study remembered having received feedback on ‘being too quiet’, ‘harder challenges’, ‘overconfidence’, ‘knowing your limits’, ‘low self‐esteem’ and ‘low self‐confidence’. Another study of third‐year medical students, this time by White and Sharma , reported similar written peer feedback themes as our clinical BDS 5 students. Amongst these, they mentioned information management, initiative and self‐direction, asking questions to learn, confidence, compassion and respect for others.…”
Section: Discussionsupporting
confidence: 65%
“…This is slightly lower than other published studies in which 70–94 % of analyzed comments were coded as positive [ 6 , 7 , 9 11 , 32 , 33 ]. The lower rate of positive comments is in line with other studies of faculty written comments to third-year clerkship students [ 9 ]; faculty written comments to residents [ 6 , 10 , 11 ] and to peers tend to be more markedly positive [ 33 ]. The perception that a comment was helpful was not associated with the valence of the comment – Cluster A, the highly helpful comments, had the same percent of positive comments as Cluster D, the least highly helpful comments.…”
Section: Discussioncontrasting
confidence: 59%
“…Research into the meaning of written comments about learners has used a single type of investigation - faculty analysis of the content of comments written by other faculty. These studies use written comments about third-year medical students [ 1 , 3 , 5 , 7 9 ] or residents [ 6 , 10 12 ] and code comments according to polarity (positive/negative) and internally-created subject categories, with category subjects varying from study to study and including such topics as “knowledge,” [ 10 ] “personal characteristics,” [ 1 ] “work ethic,” [ 9 ] “behavior,” [ 6 ] “future life as a physician,” [ 3 ] and “initiative” [ 7 ]. From this body of literature we learn that written comments are infrequently related to clinical skills [ 1 ] but often related to professional behaviors [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…49 In the context of clinical supervision, the unexpectedness of encountering insufficient engagement with learning may signal a contradictory supervisory action and evoke dissonance. write about engagement with the learning process in their comments, 54,55 although such comments can be interpreted negatively by others. 56 Therefore, strategies to counter associated stigma may be needed to implement assessments specifically designed to document learning process engagement.…”
Section: Discussionmentioning
confidence: 99%